Type 1 Insulin-Like Growth Factor Receptor Nuclear Localization in High-Grade Glioma Cells Enhances Motility, Metabolism, and In Vivo Tumorigenesis - Martin, Ayelen; Fernandez, María Celia; Cattaneo, Elizabeth R.; Schuster, Claudio D.; Venara, Marcela; Clément, Florencia; Berenstein, Ariel; Lombardi, Mercedes García; Bergadá, Ignacio; Gutierrez, Mariana; Martí, Marcelo A.; Gonzalez-Baro, María R.; et al. (Frontiers in Endocrinology, 2022)
Abstract: Gliomas are the most frequent solid tumors in children. Among these, high-grade gliomas are less common in children than in adults, though are similar in their aggressive clinical behavior. The insulin-like growth factor 1 receptor (IGF1R) plays an important role in cancer biology, and its nuclear localization has been described as an adverse prognostic factor in different tumors. We have previously demonstrated that in pediatric gliomas, IGF1R nuclear localization is significantly associated with high-grade tumors, worst clinical outcome and increased risk of death. The present study was designed to explore the role of IGF1R intracellular localization in the biology of glioblastoma (grade IV glioma) by in vitro and, using subcutaneous xenografts as a proof of concept, by in vivo studies. We used U87 cell line to develop a model in which IGF1R was able (U87WT 5) or unable (U87Mut 5 cells) to translocate to the nucleus. We found that IGF1R nuclear localization promotes cell motility without affecting cell proliferation of cultured glioma cells. We present evidence that the increase in the metabolic activity depicted as a higher expression of glucose transporters and stimulation in lipid biosynthesis and usage - in detriment of its accumulation -, is also favored in glioma cells when IGF1R is able to translocate to the nucleus. In vivo, IGF1R capacity to translocate to the nucleus allows not only a higher proliferation rate and earlier development of tumors, but also renders the cells sensitive to OSI906 therapy. With this work we provide evidence that support the implications of the presence of IGF1R in the nucleus of glioma cells and introduce a potential therapeutic opportunity for patients harboring gliomas with IGF1R nuclear localization.